Use closed reservoirs for CO2 storage and heat recovery: A two-stage brine-extraction and CO2-circulation strategy. (August 2022) - Chen, Mingjie; Al-Maktoumi, Ali; Izady, Azizallah; Cai, Jianchao; Dong, Yanhui
Highlights: An innovative operation scheme is evaluated for sequential CGS-CPG in a closed reservoir. 200 CGS-CPG models are developed and simulated in the numerical experiment. Produced brine thermal energy can reach 3.6 × 10 15 J and 7.5 WM within its lifespan. Produced CO2 thermal energy can reach 6.5 × 10 15 J and 7.0 WM within its lifespan. Abstract: Integrated CO2 (carbon dioxide) geologic storage (CGS) and CO2 plume geothermal (CPG) production provides an attractive approach not only to reduce atmospheric CO2 concentration but also to generate carbon-free geothermal energy to supplement electricity power. The current CGS-CPG studies are mostly limited to large-scale thick saline formations with open boundaries. Small to moderate scale closed-boundary reservoirs, which are typical for oil/gas fields, have rarely been evaluated for CGS-CPG. One of the major reasons is that the closed system has limited storage volume, and native brine has nowhere to escape to free storage space for injected CO2 . This study provides a solution to this issue by implementing an innovative two-stage operational strategy to realize CGS-CPG in closed reservoirs. The proposed strategy extracts pure hot brine and CO2 in two sequential stages by two separate wells, and can effectively avoid brine-CO2 separation on ground surface. A suite of numerical models is developed to evaluate the approach with a variety of reservoir conditions and operations. Results demonstrate the feasibility of our solution for implementing CGS-CPG in closed systems, and indicate the tremendous potentials to use depleted oi/gas reservoirs as the candidate fields, which widely exist in North Oman and the world.